speG Is Required for Intracellular Replication of Salmonella in Various Human Cells and Affects Its Polyamine Metabolism and Global Transcriptomes - Fang, Shiuh-Bin; Huang, Ching-Jou; Huang, Chih-Hung; Wang, Ke-Chuan; Chang, Nai-Wen; Pan, Hung-Yin; Fang, Hsu-Wei; Huang, Ming-Te; Chen, Ching-Kuo (Frontiers in Microbiology, 2017)
The speG gene has been reported to regulate polyamine metabolism in Escherichia coli and Shigella, but its role in Salmonella remains unknown. Our preliminary studies have revealed that speG widely affects the transcriptomes of infected in vitro M and Caco-2 cells and that it is required for the intracellular replication of Salmonella enterica serovar Typhimurium (S. Typhimurium) in HeLa cells. In this study, we demonstrated that speG plays a time-dependent and cell type-independent role in the intracellular replication of S. Typhimurium. Moreover, high-performance liquid chromatography of four major polyamines demonstrated putrescine, spermine, and cadaverine as the leading polyamines in S. Typhimurium. The deletion of speG significantly increased the levels of the three polyamines in intracellular S. Typhimurium, suggesting the inhibitory effect of speG on the biosynthesis of these polyamines. The deletion of speG was associated with elevated levels of these polyamines in the attenuated intracellular replication of S. Typhimurium in host cells. This result was subsequently validated by the dose-dependent suppression of intracellular proliferation after the addition of the polyamines. Furthermore, our RNA transcriptome analysis of S. Typhimurium SL1344 and its speG mutant outside and inside Caco-2 cells revealed that speG regulates the genes associated with flagellar biosynthesis, fimbrial expression, and functions of types III and I secretion systems. speG also affects the expression of genes that have been rarely reported to correlate with polyamine metabolism in Salmonella, including those associated with the periplasmic nitrate reductase system, glucarate metabolism, the phosphotransferase system, cytochromes, and the succinate reductase complex in S. Typhimurium in the mid-log growth phase, as well as those in the ilv–leu and histidine biosynthesis operons of intracellular S. Typhimurium after invasion in Caco-2 cells. In the present study, we characterized the phenotypes and transcriptome effects of speG in S. Typhimurium and reviewed the relevant literature to facilitate a more comprehensive understanding of the potential role of speG in the polyamine metabolism and virulence regulation of Salmonella.